Study on properties of an analytic function involving a generalised derivative operator - Terwase, Ajai P.; Maslina Darus (Penerbit Universiti Kebangsaan Malaysia, 2015)
In this paper, we study a new subclass of analytic functions defined by a derivative operator. Coefficient bounds, extreme point and integral transform are investigated.